Professional Socialization-The Key to Survival as a Newly Qualified Nurse - MOONEY, MARY (My University, 2007)
The impact and prevalence of professional socialization in nursing has been written about extensively. Despite the many positive developments that have taken place in nursing within the past decade, the role of professional socialization remains heavily weighted and is of particular significance to those nurses who are newly qualified. The account given by newly registered nurses in this study demonstrates that their ability and willingness to become professionally socialized determines their ease of survival at clinical level. Twelve newly qualified Irish nurses, from two separate cohorts, were interviewed to ascertain their perceptions of becoming newly qualified nurses. A grounded theory approach was used and data were analysed using thematic analysis. A category that emerged was linked very strongly with professional socialization. The respondents did not refer to professional socialization per se, but through the coding process this emerged as the linchpin of the discussion.
PUBLISHED
Keywords: Nursing